Cavitation dynamics and thermodynamic effects at elevated temperatures in a small Venturi channel. (May 2021) - Ge, Mingming; Petkovšek, Martin; Zhang, Guangjian; Jacobs, Drew; Coutier-Delgosha, Olivier
Highlights: The re-entrant jet induced cloud shedding is confirmed in hot water. Whole stages of the cavity clouds developing and collapsing are presented. Shedding dynamics of cavitation over a wide tempetature range are identified. The thermal transition and increase-decrease trend of cavity length are analyzed. Abstract: The effects of temperature on hydraulic cavitation dynamics are investigated under various operating conditions, in a close loop cavitation tunnel with a small-scale venturi type section. A systematic study is performed with temperatures varying between 24°C and 85°C, using a high-speed visualization system to observe the cavitating flow. The image processing methods provided in the paper present a quantitative comparison of the cavitation dynamics and structure development. The results show that the increase of the fluid temperature induces the growth of the cavitation volume up to about 55°C, thereafter an additional increase in temperature has the opposite effect. This evolution is interpreted as a competition between a Reynolds effect and the well-known thermal effect. Cavitation is more closely investigated within the temperature range 50°C - 65°C, to analyze the changes in the structure and the cavitation dynamics. For the prediction of thermal suppression head, the thermal effect parameter Σ which can be used empirically, is derived at the maximum cavitation length. This fluid thermodynamic parameter Σ(Ttrans ) at the transition peak can be referred to to avoid the maximum cavitation aggressiveness induced vibration or erosion for thermos-fluids around the thermal transition temperature. Finally, the factors influencing cavitation length and shedding frequency are presented and analyzed.